DIFFERENTIATED LEARNING TO IMPROVE STUDENTS' CREATIVE THINKING ABILITY - Susilawati, Samsul; Chakim, Abdulloh; Putri, Candra Avista (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Learning should be carried out interactively, inspiring, challenging, motivating, fun and meaningful, as well as accommodating the development of students' creativity, talents and potential. Students can develop physically and psychologically according to their stages. This is in accordance with the concept of differentiated learning. Differentiated learning is an attempt to harmonize the learning process in meeting the learning needs of each learner. However, the implementation of differentiated learning, especially in social studies learning, is still limited. For this reason, researchers are interested in conducting a literature review related to this, both in terms of content, process, product and learning environment. Writing this literature review aims to (1) describe the application of differentiated learning, (2) the principles and characteristics of implementing differentiated learning, (3) analyze opportunities for implementing differentiated learning in social studies learning. This literature review was obtained from scientific research articles from the 2010-2022 range using Google Scholar and obtained 50 articles with the keyword differentiated learning. From 50 articles, identification, screening, and eligibility were carried out, then 15 articles were obtained that were in accordance with the objectives of the literature review. Based on the results of the analysis of the literature review, it can be concluded that (1) the differentiated approach can be integrated with several learning models such as Problem Based Learning (PBL), Project Based Learning (PjBL) which are adapted to student learning styles; (2) differentiated learning is more interesting and can improve students' creative thinking; (3) differentiated learning can be used in social studies learning because it can accommodate students' learning needs that are tailored to students' interests, learning styles, profiles and learning readiness.